Conserved Residues in the N Terminus of Lipin-1 Are Required for Binding to Protein Phosphatase-1c, Nuclear Translocation, and Phosphatidate Phosphatase Activity - Kok, Bernard P. C. (American Society for Biochemistry and Molecular Biology, 2014)
Lipin-1 is a phosphatidate phosphatase in glycerolipid biosynthesis and signal transduction. It also serves as a transcriptional co-regulator to control lipid metabolism and adipogenesis. These functions are controlled partly by its subcellular distribution. Hyperphosphorylated lipin-1 remains sequestered in the cytosol, whereas hypophosphorylated lipin-1 translocates to the endoplasmic reticulum and nucleus. The serine/threonine protein phosphatase-1 catalytic subunit (PP-1c) is a major protein dephosphorylation enzyme. Its activity is controlled by interactions with different regulatory proteins, many of which contain conserved RVXF binding motifs. We found that lipin-1 binds to PP-1cγ through a similar HVRF binding motif. This interaction depends on Mg(2+) or Mn(2+) and is competitively inhibited by (R/H)VXF-containing peptides. Mutating the HVRF motif in the highly conserved N terminus of lipin-1 greatly decreases PP-1cγ interaction. Moreover, mutations of other residues in the N terminus of lipin-1 also modulate PP-1cγ binding. PP-1cγ binds poorly to a phosphomimetic mutant of lipin-1 and binds well to the non-phosphorylatable lipin-1 mutant. This indicates that lipin-1 is dephosphorylated before PP-1cγ binds to its HVRF motif. Importantly, mutating the HVRF motif also abrogates the nuclear translocation and phosphatidate phosphatase activity of lipin-1. In conclusion, we provide novel evidence of the importance of the lipin-1 N-terminal domain for its catalytic activity, nuclear localization, and binding to PP-1cγ.